PELAYANAN ORDO KAMILIAN TERHADAP ODGJ DI SIKKA, FLORES, MENURUT YOH 4:1-42 - Bour, Eugenius Koresy; Dhogo, Petrus Cristologus; Widyawati, Fransiska (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2024)
People with Mental Disorders (ODGJ) are a marginalized group who often receive inhumane treatment, are discriminated against, abandoned and become victims of violence. This article explores the pastoral care carried out by the Kamilian Order in Sikka, East Nusa Tenggara Province towards the ODGJ group from 2016 to 2023 and reflects on this work in the light of the Gospel of John 4:1-42. The method used is qualitative. Field data was obtained through interviews and participatory observation. The results of the research found that the Kamilian Order had implemented four superior routine programs, namely: 1) conducting professional searches and data collection on ODGJ, 2) building communication and education with patients and their families, 3) providing spiritual services, and 4) building safe houses free of shackles. Through this work, the Kamilian Order has presented a Christ who cares for and saves the small and marginalized, as is the message of the Gospel of John 4:1-42. This research concludes that the Kamilian Order has a significant concern and pastoral role in humanizing ODGJ in Sikka, NTT and realizing the gospel of liberation for marginalized people.